AB0417 Incidence of Tuberculosis in Rheumatoid Arthritis Treated with Biological Agents. (10th June 2014) - Rosales Rosado, Z.; Gόmez, A.; Peña, R.; Toledano, M.E.; Vadillo, C.; Lajas, C.; Arietti, L.; Jover, J. Ά.; Martínez, C.; Fernández, B.; Abásolo, L.
Abstract : Background: Since the introduction of the biological agents (BA) in the treatment of rheumatoid arthritis (RA) in the late 90s, in particular TNF inhibitors, there is a major concern in Rheumatology about the reactivation of latent tuberculosis (TB). In 2002 the recommendations for latent TB screening in patients receiving anti-TNF drugs were launched in Spain. Objectives: a) To describe the incidence of TB in RA treated with BA, b) To assess whether this incidence has changed over time, c) To compare the risk of developing TB by BA. Methods: We performed a retrospective observational longitudinal study from 1/1/2000 to 23/11/2013. We included subjects followed up in our outpatient clinic, diagnosed with RA according to ACR criteria 87, whom started treatment with a BA [etanercept (ETN), golimumab (GOLI), certolizumab (CTZ), infliximab (IFX), adalimumab (ADA), rituximab (RTX), abatacept (ABA), or tozilizumab (TZL)]. Our primary end point was TB infection that involved the suspension of the BA. We consider TB infection when there was a positive culture or compatible symptoms that responded to TB treatment. We also collected secondary variables: sociodemographic (age, sex); clinical (disease duration, types of BA, hospital admission, previous BA, location of TB). Statistical analysis: We used survival techniques to estimate the incidence of TB expressed per 1000 patient-year [CI 95%]. The exposure time was defined from the start date of each BA to suspension, loss of follow up or end of study (23/11/2013). We performed Cox regression models (adjusted by age, duration of RA, sex, calendar time and prior BA) to compare the risk of TB between each BA. Results: 405 RA patients were included in the study; they started 744 different courses of BA treatment, with a total follow-up of 1, 612 patient-years. Of these, 81% were women with a mean age at diagnosis of 52.5±13 years. The most frequently used drug was ADA (32%), followed by ETN (25%), IFX (21%) and RTX (14%). There were 12 cases of TB, 82% extrapulmonary, there were no deaths due to TB in our patients. Global incidence of TB was 7.4 [4.2-13.1] and tended to decrease over time (before 2002 12.0 [4.5-31.9], after 2002 6.3 [3.1-12.5]). We only registered TB cases in patients treated with anti-TNF, being IFX the drug with higher incidence (n=9, incidence 20.3 [10.5-38.9]). In the multivariate analysis we observed that the treatment with IFX compared to ETN and ADA associated significantly increased risk of developing TB (HR: 0.10 [0.01-0.8], p=0.038 and HR: 0.18 [0.04-0.9], p=0.034 respectively). Conclusions: This study describes the incidence of TB and its evolution over time in real life conditions. Following the implementation of the recommendations for detecting latent TB, the incidence has decreased in our center. We only found TB cases in anti-TNF drugs, being IFX the drug with higher risk of TB. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4517